HUMAN: PHILOSOPHY OF NATURAL AND ARTIFICIAL INTELLIGENCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the relationship between natural human intelligence and artificial intelligence from both natural and technological perspectives. It highlights how artificial intelligence is increasingly becoming a powerful technical tool in the modern world, while also pointing out the absence of ethical and moral standards within such systems. Despite sharing common features like algorithmic thinking, learning, and adaptability, the article offers a philosophical perspective on the fundamental differences between artificial and natural intelligence, particularly in terms of their technological and human aspects.